(untitled) (FAVE Sección Ciencias Agrarias, 2025)
Dairy farms in the Pampas Region are characterized according to their scale, business organization, productive management, and productive and economic results. With the information provided form the sectorial survey of dairy farmers performed by INTA, synthetic indicators were constructed to identify types of dairy farms, based on dimensionality reduction methodologies and cluster analysis. Three defined groups were highlighted, one with low competitive performance, low scale, individual and family business organization, with application of low management technology, low production results and negative profitability. A second group of dairy farms with regular competitive performance, average scale and production results, with improved management and business organization, but insufficient to obtain profitability. Finally, a group of highly competitive dairy farms with higher scale and superior level of business organization, productive management and technology applied, with better productive and economic results than obtained in the other two groups. The three groups identified revealed a representativeness of 22%, 46% and 32% respectively among farms involved in the INTA survey.